Urgensitas Penguatan Kompetensi Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama dalam Mengawal Pertumbuhan Industri Keuangan Syariah di Indonesia - Suhartono Suhartono (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2017)
The growth of the Islamic financial industry in Indonesia requires the support of a competent and effective dispute resolution system. This research examines the urgency of strengthening the competence of sharia economic dispute resolution in the Religious Courts as an important instrument in guarding the development of the halal industry. The research method uses a qualitative approach with analysis of literature, legislation, and case studies related to the performance of the Religious Courts in handling sharia economic disputes. The results showed that human resource capacity, comprehensive understanding of sharia principles, and harmonization of regulations are still the main challenges. Efforts are needed to increase the competence of judges, optimize mediation institutions, and synergize with Islamic financial authorities to strengthen legal certainty and public trust. Thus, the Religious Courts can play a more effective role in encouraging the sustainable growth of the Islamic finance industry in Indonesia.